# -8h-6=h+417

## Simple and best practice solution for -8h-6=h+417 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for -8h-6=h+417 equation:

Simplifying
-8h + -6 = h + 417
Reorder the terms:
-6 + -8h = h + 417
Reorder the terms:
-6 + -8h = 417 + h
Solving
-6 + -8h = 417 + h
Solving for variable 'h'.
Move all terms containing h to the left, all other terms to the right.
Add '-1h' to each side of the equation.
-6 + -8h + -1h = 417 + h + -1h
Combine like terms: -8h + -1h = -9h
-6 + -9h = 417 + h + -1h
Combine like terms: h + -1h = 0
-6 + -9h = 417 + 0
-6 + -9h = 417
Add '6' to each side of the equation.
-6 + 6 + -9h = 417 + 6
Combine like terms: -6 + 6 = 0
0 + -9h = 417 + 6
-9h = 417 + 6
Combine like terms: 417 + 6 = 423
-9h = 423
Divide each side by '-9'.
h = -47
Simplifying
h = -47